Conservation Status of Stephensoniella brevipedunculata Kashyap, an Endangered Liverwort - Verma, Praveen Kumar; Rawat, Krishana Kumar; Kumar, Vishavjit; Chandra, Anup (Journal of the Bombay Natural History Society (JBNHS), 2018)
No Abstract.